Tissue-resident myeloid and histiocytic cells in health and disease: novel emerging concepts : critical review - Valent, Peter; Wojta, Johann; Kovanen, Petri T.; Hermine, Olivier; Fend, Falko; Sotlar, Karl; Greinix, Hildegard; Geissler, Klaus; Hartmann, Karin; Schwaab, Juliana; Herling, Marco; Boccuni, Laura; et al. (American journal of hematology, 2025)
Although all myeloid cells are considered to derive from hematopoietic stem cells, the cells in each myeloid lineage are heterogeneous populations, and their distribution and functions vary, depending on underlying physiologic and pathologic processes, age, sex, and genetic and epigenetic signatures. In general, myeloid cells can be separated into circulating and tissue-resident cells. Tissue-resident myeloid cells can further be divided into cells derived from circulating monocytes, circulating stem cells, or local tissue-restricted stem or progenitor cells. Depending on underlying diseases and co-morbidities, the phenotype, function, and distribution of these cells may change substantially. In this article, we discuss new developments in the field and related emerging concepts around tissue-resident myeloid cells and their role and function in reactive and clonal disorders. Cell types reviewed in depth in this article include monocytes, macrophages, histiocytes, dendritic cells, and tissue mast cells, with a focus on inflammatory disease processes, vascular pathologies, solid tumors, and hematopoietic malignancies. Moreover, the current article provides an update on patient-related and disease-related diagnostic and prognostic variables, multi-parametric prognostic scoring systems, and therapeutic options and algorithms in these neoplasms. Finally, our article provides an overview on the emerging role and impact of precision medicine approaches, translational research, and artificial intelligence in the diagnosis, prognostication, and management of monocytic, histiocytic, and mast cell disorders.